Legal Perspective On Internet Banking In Malaysia - Radhakrishna, Gita (2007)
The research objective is to investigate five questions in relation to Malaysia. Firstly, the incidence of fraud in internet banking transactions, focusing on the offence of 'phishing' or 'identity theft'; secondly, the level of adoption of internet banking by legal firms in Malaysia; thirly, the perception of Malaysian lawyers n the adequacy of current statutory provisions and regulations for the procecution of fraud in internet banking; fourthly, the legal issues in internet banking contracts between the Bank and customers; and fifthly, the problems if any in adducing electronic evidence in its prosecution.